Neuroprotective effect of a new photobiomodulation technique against Aβ25–35 peptide–induced toxicity in mice: Novel hypothesis for therapeutic approach of Alzheimer's disease suggested. Issue 1 (1st February 2018) - Blivet, Guillaume; Meunier, Johann; Roman, Francois J.; Touchon, Jacques
Abstract: Introduction: Photobiomodulation was assessed as a novel treatment of Alzheimer's disease (AD) by the use of a new device RGn500 combining photonic and magnetic emissions in a mouse model of AD. Methods: Following the injection of amyloid β 25‐35 peptide in male Swiss mice, RGn500 was applied once a day for 7 days either on the top of the head or the center of abdomen or both. Results: RGn500 daily application for 10 min produced a neuroprotective effect on the neurotoxic effects of amyloid β 25‐35 peptide injection when this type of photobiomodulation was applied both on the head and on the abdomen. Protection was demonstrated by memory restoration and on the normalization of key markers of AD (amyloid β 1‐42, pTau), oxidative stress (lipid peroxidation), apoptosis (Bax/Bcl2) and neuroinflammation. Discussion: RGn500 displays therapeutic efficacy similar to other pharmacological approaches evaluated in this model of AD.